Properties of fly ash geopolymer concrete designed by Taguchi method - Olivia, Monita; Nikraz, Hamid (Elsevier Ltd, 2011)
This paper presents an optimization of fly ash geopolymer mixtures by Taguchi method,and a study on the mechanical properties and durability of concrete produced from the optimal mixes. A total of nine mixtures were evaluated by considering the effects of aggregate content, alkaline solution to fly ash ratio, sodium silicate to sodium hydroxide ratio, and curing method. Ordinary Portland Cement (OPC) concrete of 55 MPa strength was used as a control mix. Three optimal mixtures (T4, T7 and T10) were identified. Results show that the geopolymer concrete can be produced with of 55 MPa at 28 days. They had higher tensile and flexural strength, produced less expansion and drying shrinkage, and showed moduli of elasticity that were 14.9-28.8% lowerthan those of the OPC control mix. The compressive strength of all geopolymer mixtures changed significantly at each wetting-drying cycle, but the weight losses were higher than that of the OPC concrete. Half-cell potential measurement showed that the geopolymer mixes were generally more prone to corrosion, although showed low-level corrosion activity and exhibited times to failure that were 3.86-5.70 times longer than those of the OPC concrete. The test results confirmed that the mechanical properties of the geopolymer mixtures tested are competitive with those of OPC concrete and provide a more durable alternative to the OPC concrete in a seawater environment.http://dx.doi.org/10.1016/j.matdes.2011.10.036